The Cost of Employee Stock Option Grants: An Empirical Analysis - Marquardt, Carol A. (Journal of Accounting Research, 2002)
This study presents empirical evidence on the ex post costs of employee stock option (ESO) grants to issuing firms and examines whether the Black–Scholes [1973] model provides reasonable estimates of these values. Because there are no market prices for ESOs, the traditional avenues for testing option–pricing models are unavailable. This research relies instead on techniques from the economic forecasting literature, viewing model values as forecasts of the options’ payoff. The theoretically appropriate rate at which to discount ESO payoffs is derived under the maintained hypothesis that the Black–Scholes model is valid. This rate is used in estimating ex post ESO costs at the time of grant, which are then compared with Black–Scholes estimates using Theil’s [1966] tests of forecast rationality. Based on a sample of 966 ESO grants over 1963–1984, the results suggest that the Black–Scholes model, adjusted for concavity in the time to exercise using the Hemmer, Matsunaga, and Shevlin [1994] procedure, appears to provide reasonable estimates of ex post ESO costs for the average ESO grant. However, there is significant variability in the amount of model error on an individual grant basis.